1988
DOI: 10.1021/bi00413a042
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic fluorescence properties of the bacterial luciferase intermediates

Abstract: Three fluorescent species produced by the reaction of bacterial luciferase from Vibrio harveyi with its substrates have the same dynamic fluorescence properties, namely, a dominant fluorescence decay of lifetime of 10 ns and a rotational correlation time of 100 ns at 2 degrees C. These three species are the metastable intermediate formed with the two substrates FMNH2 and O2, both in its low-fluorescence form and in its high-fluorescence form following light irradiation, and the fluorescent transient formed on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
31
0

Year Published

1989
1989
2005
2005

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 34 publications
(54 reference statements)
5
31
0
Order By: Relevance
“…Emission decay measurements were made with laser system and single-photon counting Petushkov et al electronics described in detail elsewhere (Lee et al, 1989b). The method of data collection and analysis was as adequately detailed elsewhere (Lee et al, 1988(Lee et al, , 1989a(Lee et al, ,b, 1991b, except with a few modifications. The sample was contained in a 3 mL thermostated cuvette, and the path lengths for excitation and emission were 10 mm.…”
Section: Methodsmentioning
confidence: 99%
“…Emission decay measurements were made with laser system and single-photon counting Petushkov et al electronics described in detail elsewhere (Lee et al, 1989b). The method of data collection and analysis was as adequately detailed elsewhere (Lee et al, 1988(Lee et al, , 1989a(Lee et al, ,b, 1991b, except with a few modifications. The sample was contained in a 3 mL thermostated cuvette, and the path lengths for excitation and emission were 10 mm.…”
Section: Methodsmentioning
confidence: 99%
“…It can be shown that for a spherical body measured at 2°C, 4 (in units of ns) is roughly equal to the molecular mass of the protein (in kDa). Dynamic fluorescence measurements of ANS bound to the wild-type luciferase and the fusion proteins in peak I and II were performed by laser excitation and single photon counting electronics (18).…”
mentioning
confidence: 99%
“…' The absorption spectrum of I1 is typical of a 4a,5-dihydroflavin, and it is weakly fluorescent, with an emission maximum around 500 nm (Hastings et al, 1973;Lee et al, 1988). The fluorescence quantum +Supported by grants from the National Science Foundation (DMB85-12361 and PCM 83-12669) and the National Institutes of Health (GM-28139, RR-02015, and RR-02389).…”
mentioning
confidence: 99%
“…The fluorescence quantum +Supported by grants from the National Science Foundation (DMB85-12361 and PCM 83-12669) and the National Institutes of Health (GM-28139, RR-02015, and RR-02389). yield is increased severalfold to 0.3 by irradiation with light Tu, 1979Tu, , 1986Lee et al, 1988).…”
mentioning
confidence: 99%